High-level expression of rat PC12 tyrosine hydroxylase cDNA in Escherichia coli: purification and characterization of the cloned enzyme. - Wang, Y H (1991)
A rat cDNA containing the complete coding sequence for rat tyrosine hydroxylase (tyrosine 3-monooxygenase, EC 1.14.16.2) was isolated from a rat PC12 cDNA library and subcloned in a bacterial expression plasmid, and large amounts of functional enzyme were produced in Escherichia coli. The recombinant enzyme was purified approximately 20-fold to a final specific activity of 1.8 mumol/min per mg of protein, with a yield of 30%. As much as 1 mg of pure protein could be obtained from 1 g of wet bacterial cells. The purified hydroxylase was shown to be homogeneous by denaturing polyacrylamide electrophoresis and isoelectric focusing. Amino acid analysis of the N terminus (25 residues) revealed 100% identity with rat PC12 tyrosine hydroxylase, as deduced from its cDNA sequence. Several of the kinetic properties of the recombinant enzyme resembled those of the native PC12 hydroxylase. However, in contrast to the native enzyme, the purified recombinant hydroxylase was shown to be in an activated form. Phosphorylation with cAMP-dependent protein kinase resulted in stoichiometric incorporation of phosphate, but the kinetic profile of the recombinant enzyme was unaffected. Several clues to these differences are considered that may provide insight into the structural features important to the regulation of tyrosine hydroxylase.